Antidepressants for anorexia nervosa - Claudino, A. M.; Hay, P.; Lima, M. S.; Bacaltchuk, J.; Schmidt, U.; Treasure, J. (Wiley-Blackwell, 2006)
Background Anorexia Nervosa ( AN) is an illness characterised by extreme concern about body weight and shape, severe self-imposed weight loss, and endocrine dysfunction. In spite of its high mortality, morbidity and chronicity, there are few intervention studies on the subject.Objectives The aim of this review was to evaluate the efficacy and acceptability of antidepressant drugs in the treatment of acute AN.Search strategy The strategy comprised of database searches of the Cochrane Collaboration Depression, Anxiety and Neurosis Controlled Trials Register, MEDLINE (1966 to April 28th, 2005), EMBASE (1980 to week 36, 2004), PsycINFO (1969 to August week 5, 2004), handsearching the International Journal of Eating Disorders and searching the reference lists of all papers selected. Personal letters were sent to researchers in the field requesting information on unpublished or in-progress trials.Selection criteria All randomised controlled trials of antidepressant treatment for AN patients, as de fined by the Diagnostic and Statistical Manual, fourth edition (DSM-IV) or similar international criteria, were selected.Data collection and analysis Quality ratings were made giving consideration to the strong relationship between allocation concealment and potential for bias in the results; studies meeting criteria A and B were included. Trials were excluded if non-completion rates were above 50%. The standardised mean difference and relative risk were used for continuous data and dichotomous data comparisons, respectively. Whenever possible, analyses were performed according to intention- to-treat principles. Heterogeneity was tested with the I-squared statistic. Weight change was the primary outcome. Secondary outcomes were severity of eating disorder, depression and anxiety symptoms, and global clinical state. Acceptability of treatment was evaluated by considering non-completion rates.Main results Only seven studies were included. Major methodological limitations such as small trial size and large confidence intervals decreased the power of the studies to detect differences between treatments, and meta-analysis of data was not possible for the majority of outcomes. Four placebo-controlled trials did not find evidence that antidepressants improved weight gain, eating disorder or associated psychopathology. Isolated findings, favouring amineptine and nortriptyline, emerged from the antidepressant versus antidepressant comparisons, but cannot be conceived as evidence of efficacy of a specific drug or class of antidepressant in light of the findings from the placebo comparisons. Non-completion rates were similar between the compared groups.Authors' conclusions A lack of quality information precludes us from drawing de finite conclusions or recommendations on the use of antidepressants in acute AN. Future studies testing safer and more tolerable antidepressants in larger, well designed trials are needed to provide guidance for clinical practice.